Theoretical validation of the properties of SnO2 nanostructure grown by Robust Spray pyrolysis technique for formaldehyde gas sensor. (2022) - Doubi, Youssef; Hartiti, Bouchaib; Siadat, Maryam; Ziti, Ahmed; Stitou, Mohamed; Joel Tchognia Nkuissi, Hervé; Labrim, Hicham; Fadili, Salah; Tahri, Mounia; Thevenin, Philippe; Losson, Etienne
Abstract: In this work, we synthesis the SnO2 thin layers by low-cost spray pyrolysis, the thin layers were analyzed using X-ray diffraction, Raman spectroscopy, Scanning electron microscopy (SEM), and UV–Visible spectrophotometer. The structural studies showed that SnO2 thin layers are of Rutile phase with strong preferred direction along (1 1 0) plan. The SEM image showed that SnO2 thin layers have a roughness and porous surfaces, which proved that SnO2 layers are suitable for gas sensor applications. The energy band gap (Eg) has been calculated from the transmittance curve and certified the semiconducting properties with a Eg = 3.65 eV. The Ab-initio method was applied based on the density functional theory (DFT) using the Wien2K code. The generalized gradient approximation and MBJ potential method have been utilized to determine the band structure, density of states, and optical properties of tin dioxide material. Our theoretical results are in good agreement with the obtained practically.